Secondary metabolites from stem bark of Garcinia beccarii pierre and Garcinia cuneifolia pierre - Arumugam, A. Muniandy (2017)
The genus Garcinia is from the family Guttiferae of evergreen trees and shrubs distributed in tropical Asia, Africa and Polynesia. The genus Garcinia is known to be a rich source of polyisoprenylated benzophenones and xanthones. Medium scale extractions of the grounded stem bark of Garcinia beccarii Pierre and Garcinia cuneifolia Pierre were conducted by using the solvent extraction method at room temperature for three days. The extracts afforded some xanthones and triterpenoids. These compounds were isolated by using various chromatographic techniques and their structures were elucidated by using spectroscopy techniques such as NMR, GC-MS and FTIR. Bioassays such as cytotoxic activities and antimicrobial screenings were investigated by using on the crude extracts of the two plants. Four xanthones namely rubraxanthone, trapezifolixanthone, α-mangostin and β-mangostin were isolated from the chloroform and ethyl acetate extracts of the stem bark of Garcinia beccarii Pierre. Two xanthones, dulxanthone C and osajaxanthone were obtained from the chloroform extract of the stem bark of Garcinia cuneifolia Pierre. Two common terpenoids were also obtained from both plants. These are stigmasterol from both plants, while beta sitosterol acetate was only obtained from the hexane crude extract of the stem bark of Garcinia cuneifolia Pierre. The hexane extract of Garcinia beccarii Pierregave low IC50 values against the MCF 7 and HL 60 cancer lines. The antimicrobial screening was also carried out using six bacteria, namely Bacillus Subtilis B29, Bacillus Subtilis B125, Staphylococcus aureus, Staphylococcus epidermidis, Methicillin Resistant Staphylococcus aureus and Streptococcus sp. Only low to moderate inhibition towards these bacteria was observed.